The Effect of Organizational Climate in Job Satisfaction Among Faculty Members at Jordanian Private Universities - Al- Refaie, Jasser (Jordan Journal of Educational Sciences, 2007)
This study aimed at identifying the prevailing forms of organizational climate at private universities in Jordan.and Their effect on the degree of job satisfaction of teaching staff at these universities. To collect information , two instruments were used which consisted of two questionnaires. One of them was used to assess The prevailing organizational climate at Jordanian private universities, as perceived by teaching staff. It consisted 52 items. The other was used to measure the degree of job satisfaction of teaching staff at these universities. It consisted 60 items. The study sample consisted 352 teaching staff members. Appropriate statistical methods were used to analyze the data. The study concluded that non – existence of statistically significant differences that could be attributed to the variables of gender, academic rank and teaching experience at all dimensions of organizational climate. It also showed the existence of statistically significant differences that could be attributed to the variable of faculty. The Differences were to the advantage of human faculties over scientific faculties at all dimensions of organizational climate.The findings of the study revealed a medium degree of satisfaction of teaching staff at all domains of job satisfaction, and there were no statistically significant differences that could be attributed to the variables of gender, academic rank and teaching experience at the scale of job satisfaction.The findings also showed the existence of statistically significant differences that could be attributed to the variable of organizational climate at the scale of job satisfaction. The differences were to the advantage of positive climate over negative climate one.The study, finally, a set of recommendations based on its concluded findings.(